Clinical, histological, and histomorphometrical comparison of CenoBone® with and without plasma rich in growth factor for edentulous ridge preservation in the dental sockets - Farshad Keshavarzi; Fateme Ahrari; Maryam Seyedmajidi; Maryam Ziaei; Ali Bijani; Niloofar Jenabian (Wolters Kluwer Medknow Publications, 2023)
Background: The aim of this study was to compare the clinical, histological, and histomorphometrical outcomes of CenoBone® allograft with and without plasma rich in growth factor (PRGF) for the preservation of edentulous ridge in the dental sockets. Materials and Methods: This study is experimental clinical trial that 14 dental sockets were included the sockets required ridge preservation followed by implant placement in the premolar and molar of the mandible. After extraction of the teeth, the CenoBone® allograft and PRGF were used in the test group and CenoBone® allograft was used alone in the control group. During the first stage of surgery and 5 months later, in the second stage of surgery (implant placement), the vertical changes of the ridge were measured. Furthermore, using Core-Biopsy in the second stage of surgery, criteria of histologic and histomorphometric were determined. Data were analyzed with t-test, Mann-Whitney U-test, and Fisher's exact test at the level of significance of P < 0.05. Results: The mean trabecular thickness in the test group (52.18 ± 5.53) was significantly higher than that in the control group (41.53 ± 10.40) (P = 0.344). However, there were no significant differences in the mean values of vertical bone absorption, bone percentage, remaining biomaterials, inflammation, and blood vessels between the two groups. There was no case of foreign body reaction and the bone was vital in all the cases and in direct contact with the biomaterial. Conclusion: Although CenoBone® allograft with PRGF was effective in some histomorphometric factors such as trabecular thickness, it did not lead to significant clinical changes.